Beda Makanan, Beda Kemampuan Perhatian : Studi Eksperimen tentang pengaruh Glycemic Index Caution Terhadap Kemampuan Deteksi Sinyal - Farizi, Zulfikar Ali; Nuqul, Fathul Lubabin (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2013)
In some nations have different eating patterns with other nations. There is consuming rice, sago, wheat and so on. Several studies have shown that meal consumption and types of food affect a person’s cognition process. One of them is attentions. Based on Jenkins’s study (1980) is known carbohydrate itself is divided by the speed of revamped into glucose in the body is divided into two, namely carbohydrates are quickly revamped into glucose or carbohydrate and high Glycemic index carbohydrates are slowly revamped into glucose or carbohydrate low glycemic index. When a person consumes carbohydrate at a rate of speed of revamped into a different glucose certainly it will affect the brain’s attention system. Attention is the ability to filter out some of the incoming stimulus of mental activity and focus on one the most important stimulus. Capability is very useful for human attention, because attention is the first gate of someone cognition processes. The research uses Crossover Experiment Design, and involves 20 graduate students as experiment subject. They are divided into 2 groups (high glycemic; rice, and low glycemic food; ubi). Subjects selected by controlling a few factor, such as, they has normal Intelligence, They has not severe disease and they are not overweight. To measure the attention ability used Attention Distraction. The results showed that the group fed high-glycemic carbohydrates (rice), have higher attention capacity compared with the provision of low glycemic carbohydrates (sweet potatoes). These results are consistent in the treatment of crossover.